Modal Sosial untuk Kemandirian Ekonomi Santri: Studi Kasus di Pesantren Al-Amin Tasikmalaya - Geytsa Yumna Rabbania Rahman; Gunawan (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Social capital is one of the key elements in the independence of educational institutions such as Islamic boarding schools. This paper aims to analyze the role of social capital in promoting the economic independence of students through the embroidery industry at Pondok Pesantren Al-Amin Tasikmalaya. Using Robert D. Putnam's social capital theory framework, this study focuses on networks, norms, and trust. This descriptive qualitative research provides an in-depth description of social phenomena through observation, in-depth interviews with various stakeholders (school principal, vice principal, embroidery teachers, garment managers, student representatives, and local community members), and documentation at Pondok Pesantren Al-Amin Tasikmalaya. Data was analyzed interactively (reduction, presentation, drawing conclusions) and verified through triangulation. The research findings indicate that the Al-Amin Islamic Boarding School successfully manages the embroidery industry as a comprehensive economic empowerment strategy. This model is fundamentally supported by the manifestation of strong social capital: active networks (through the absorption of graduates into partner factories, strategic industrial partnerships, and a maklun system that empowers the surrounding community) that open economic opportunities and market access for students; emphasized norms (product quality, business ethics, and internal solidarity) that shape professional work ethics and student integrity; and trust as the glue for harmonious collaboration between the boarding school, students, and industry stakeholders. The social capital formed through students' direct involvement in industry and embroidery skill training influences the development of their potential, skills, and ultimately, economic independence, preparing them to become competitive individuals. This paper provides deep insights into how social capital can serve as a key pillar in achieving economic independence for individual students within religious educational institutions.